Ambient air pollution and epileptic seizures: A panel study in Australia. Issue 7 (26th April 2022) - Chen, Zhuying; Yu, Wenhua; Xu, Rongbin; Karoly, Philippa J.; Maturana, Matias I.; Payne, Daniel E.; Li, Lyra; Nurse, Ewan S.; Freestone, Dean R.; Li, Shanshan; Burkitt, Anthony N.; Cook, Mark J.; et al.
Abstract: Objective: Emerging evidence has shown that ambient air pollution affects brain health, but little is known about its effect on epileptic seizures. This work aimed to assess the association between daily exposure to ambient air pollution and the risk of epileptic seizures. Methods: This study used epileptic seizure data from two independent data sources (NeuroVista and Seer App seizure diary). In the NeuroVista data set, 3273 seizures were recorded using intracranial electroencephalography (iEEG) from 15 participants with refractory focal epilepsy in Australia in 2010–2012. In the seizure diary data set, 3419 self‐reported seizures were collected through a mobile application from 34 participants with epilepsy in Australia in 2018–2021. Daily average concentrations of carbon monoxide (CO), nitrogen dioxide (NO2 ), ozone (O3 ), particulate matter ≤10 μm in diameter (PM10 ), and sulfur dioxide (SO2 ) were retrieved from the Environment Protection Authority (EPA) based on participants' postcodes. A patient‐time‐stratified case‐crossover design with the conditional Poisson regression model was used to determine the associations between air pollutants and epileptic seizures. Results: A significant association between CO concentrations and epileptic seizure risks was observed, with an increased seizure risk of 4% (relative risk [RR]: 1.04, 95% confidence interval [CI]: 1.01–1.07) for an interquartile range (IQR) increase of CO concentrations (0.13 parts per million), whereas no significant associations were found for the other four air pollutants in the whole study population. Female participants had a significantly increased risk of seizures when exposed to elevated CO and NO2, with RRs of 1.05 (95% CI: 1.01–1.08) and 1.09 (95% CI: 1.01–1.16), respectively. In addition, a significant association was observed between CO and the risk of subclinical seizures (RR: 1.20, 95% CI: 1.12–1.28). Significance: Daily exposure to elevated CO concentrations may be associated with an increased risk of epileptic seizures, especially for subclinical seizures.